2006
DOI: 10.1177/0310057x0603400302
|View full text |Cite
|
Sign up to set email alerts
|

Recovery after Prolonged Anaesthesia for Acoustic Neuroma Surgery: Desflurane versus Isoflurane

Abstract: In this study, 33 patients were randomly assigned to receive desflurane (D) or isoflurane (I) for acoustic neuroma surgery. The time from end of the procedure to spontaneous breathing, extubation, eye-opening, hand-squeezing to command, and ability to state name, birthdate and phone number were recorded. The Steward recovery score was also recorded every five minutes during the first 20 minutes postoperatively and then every 10 to 15 minutes. Groups were similar regarding patient characteristics, depth of anae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 21 publications
1
22
1
Order By: Relevance
“…Though direct comparisons cannot be made, the emergence/extubation/recovery time in the studies where N 2 O was used were similar to our study results. [ 1 10 12 13 ] However, in studies where N 2 O was not used the emergence/extubation/recovery times were longer than that of our study. [ 5 14 ] The difference in the recovery could be attributed to use of N 2 O.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Though direct comparisons cannot be made, the emergence/extubation/recovery time in the studies where N 2 O was used were similar to our study results. [ 1 10 12 13 ] However, in studies where N 2 O was not used the emergence/extubation/recovery times were longer than that of our study. [ 5 14 ] The difference in the recovery could be attributed to use of N 2 O.…”
Section: Discussioncontrasting
confidence: 51%
“…[ 5 ] Bertrand and associates reported the emergence time and full recovery time with desflurane to be 14.9 ± 2.4 min and 22.1 ± 3.1 min respectively in patients undergoing acustic neuroma surgery. [ 13 ] Gauthier et al . reported the emergence time, extubation time and orientation time in sevoflurane group to be 15.0 ± 8.7 min, 19.9 ± 12.7 min and 32.9 ± 26 min respectively in neurosurgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rohm et al (4) demonstrated that patients undergoing prolonged surgical procedures (>150 min) showed faster recovery and required lower expenditure after a desflurane/fentanyl regimen than a propofol/remifentanil regimen. Faster recovery following desflurane, compared with isoflurane, may be desirable after long surgical procedures (>5 hours) (6), enabling the patient's full cooperation and facilitating the early diagnosis of any potential neurological deficit. Nordmann et al (21) also demonstrated that increasing the duration of inhalation anesthesia is associated with slower emergence and recovery in children, but this effect was less evident with desflurane compared with isoflurane.…”
Section: Discussionmentioning
confidence: 99%
“…The major advantages include rapid induction and recovery (2,3), lower cost (4), and myocardial protection during cardiac surgery (5). Due to its lower blood-gas partition coefficient (0.42), the ratio of the dissolved amount in the blood to the amount in the alveolar gas in contact with the blood, desflurane has been clearly proven to provide a shorter time to extubation compared with sevoflurane (20% reduction) (2) and isoflurane (34% reduction) (3), especially in those individuals undergoing prolonged surgical procedures (4,6). …”
Section: Introductionmentioning
confidence: 99%
“…The effects on the brain can be monitored with continuous electroencephalography. The anesthetic effects of isoflurane are brief; however, with longer use, e.g., with days of continuous administration, sedation can be prolonged, possibly due to isoflurane going into fat stores and then redistributing [5]. Ideally, an anesthetist who is familiar with isoflurane should be involved.…”
mentioning
confidence: 99%